Development of Teaching Materials for Serialized Images of Listening to Stories Using Powerpoints to Improve Arabic Language Skills in Junior High School Students of Baitul Arqam Sumedang Islamic Boarding School - Supala Supala; Mariana Mariana; Ahmad Rifai (MANAZHIM, 2023)
Currently, learning media in various schools has become a very important element in the teaching process, because it can contain messages that will be conveyed to students / students during learning using illustrated teaching materials, one of which is at Baitul Arqam Junior High School which will try to apply learning by using PowerPoint-based serial image media in improving students' storytelling skills. This research uses a descriptive method of qualitative research type analysis. The descriptive method is a method in a study to solve, obtain information about a situation, assess, and determine the symptoms found, see or analyze the relationship between existing variables. The results of ni research showed that learning Arabic storytelling method by obtaining a sekor bbased on the Hasil table by students of Baitul Arqam Sumedang Junior High School obtained a score of 80% representation, which is very good. So, it can be concluded that the use of PowerPoint-based serialized image media is effectively applied to improve students' ability to tell Arabic stories.